1990
DOI: 10.1002/art.1780330305
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose methotrexate compared with auranofin in adult rheumatoid arthritis

Abstract: Weekly treatment with low-dose oral methotrexate (MTX) was compared with daily auranofin (AUR) treatment in a 36-week double-blind, randomized, multicenter study of 281 patients with active, adult-onset rheumatoid arthritis. Both treatment groups showed significant improvement by the usual measures of clinical efficacy. The response with MTX occurred earlier and was consistently greater than that with AUR. An intent-to-treat analysis showed significantly greater improvement (P < 0.01) with MTX for painful and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(48 citation statements)
references
References 18 publications
(6 reference statements)
1
46
0
1
Order By: Relevance
“…In our initial investigation of the clinical results of the treatment, we observed a greater improvement in the MTX group than in the AUR group (11). An intent-to-treat analysis of all patients confirmed the clinical superiority of MTX.…”
Section: Discussionmentioning
confidence: 69%
“…In our initial investigation of the clinical results of the treatment, we observed a greater improvement in the MTX group than in the AUR group (11). An intent-to-treat analysis of all patients confirmed the clinical superiority of MTX.…”
Section: Discussionmentioning
confidence: 69%
“…This long-term open study was an extension of our previous study comparing MTX and auranofin, in which MTX was found to be not only more effective, but also less toxic than auranofin over a 36-week period (3). Following completion of the randomized trial, 123 patients were enrolled in this 5-year open extension study of MTX.…”
Section: Discussionmentioning
confidence: 99%
“…During the open study, adjustments in the MTX dosage were allowed; the maximum dosage was 20 mglweek. Clinical evaluations were performed every 12 weeks and included determinations of the number of painful joints, number of swollen joints, joint tendernesdpain index, joint swelling index, duration of morning stiffness, and patient and physician global assessments (3). A modified Stanford Health Assessment Questionnaire (MHAQ) (4) was completed at baseline, yearly, and at the last study visit.…”
Section: Methodsmentioning
confidence: 99%
“…One of these (Schmid FR et al: unpublished observations) was a small unpublished trial, and its exclusion does not affect analytic results. Since we wished to choose regimens that offered as large as possible an efficacy difference between drug and placebo, we excluded 1 auranofin arm in 1 trial, since evidence (11,12) suggests it is relatively weak. Six of the 7 ACR core set measures were included in these trials, but like many completed RA trials, 4 of the 5 trials did not include an assessment of functional status.…”
Section: Methodsmentioning
confidence: 99%